Clinical Cases in LAA Occlusion Indication, Techniques, Devices, Implantation - Bergmann, Martin W.; Tzikas, Apostolos; Wunderlich, Nina C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This concise practical guide is designed to facilitate the clinical decision-making process in the management of LAA occlusion procedures by reviewing a number of cases and defining the various diagnostic and management decisions open to clinicians. Clinical Cases in LAA Occlusion is well illustrated but concise, enabling the reader to obtain relevant information regarding both standard and unusual cases in a rapid, easy to digest format. Each case includes a narrative description and patient management tips.
1 Background -- 2 Safety and efficacy of LAA closure -- 3 Anatomy and imaging of the LAA -- 4 Access to the left atrium -- 5 WATCHMAN implantation step-by-step -- 6 WATCHMAN case examples -- 7 AMULET implantation step-by-step -- 8 AMULET case examples -- 9 Prevention and Management of complications -- 10 Combined procedures.
Keywords: Medicine; Interventional radiology; Cardiology; Cardiac surgery; Medicine & Public Health; Cardiology; Interventional radiology; Cardiac surgery